Evidence for high‐temperature in situ nifH transcription in an alkaline hot spring of Lower Geyser Basin, Yellowstone National Park - Sara T. Loiacono; D'Arcy R. Meyer‐Dombard; Jeff R. Havig; Amisha T. Poret‐Peterson; Hilairy E. Hartnett; Everett L. Shock (Environmental Microbiology, 2012)
Summary Genes encoding nitrogenase ( nifH ) were amplified from sediment and photosynthetic mat samples collected in the outflow channel of Mound Spring, an alkaline thermal feature in Yellowstone National Park. Results indicate the genetic capacity for nitrogen fixation over the entire range of temperatures sampled (57.2°C to 80.2°C). Amplification of environmental nifH transcripts revealed in situ expression of nifH genes at temperatures up to 72.7°C. However, we were unable to amplify transcripts of nifH at the higher‐temperature locations (> 72.7°C). These results indicate that microbes at the highest temperature sites contain the genetic capacity to fix nitrogen, yet either do not express nifH or do so only transiently. Field measurements of nitrate and ammonium show fixed nitrogen limitation as temperature decreases along the outflow channel, suggesting nifH expression in response to the downstream decrease in bioavailable nitrogen. Nitrogen stable isotope values of Mound Spring sediment communities further support geochemical and genetic data. DNA and cDNA nifH amplicons form several unique phylogenetic clades, some of which appear to represent novel nifH sequences in both photosynthetic and chemosynthetic microbial communities. This is the first report of in situ nifH expression in strictly chemosynthetic zones of terrestrial (non‐marine) hydrothermal systems, and sets a new upper temperature limit (72.7°C) for nitrogen fixation in alkaline, terrestrial hydrothermal environments.